Charlie bone and the castle of mirrors eaudiobook - Nimmo, Jenny (Children of the Red King, 2006)
Charlie Bone’s power takes on a new dimension at Bloor’s Academy in Charlie Bone and the Castle of Mirrors . There is a new cast of characters, including Mr. Pilgrim’s replacement, Tantalus Ebony, and the mysterious new student Joshua Tilpin, who appears to be magnetic. Billy has been adopted by a mysterious couple and is locked up in an odd place called The Passing House. Meanwhile, Charlie and Olivia discover the secret of the Castle of Mirrors, and along with Uncle Paton, they must free Billy before it is too late.